Computer Learning and Teaching Obstacles in governmental Schools in Northern Directorates of Palestine from Teaching and Students Point of Views - Adel Fayes Mahmoud Al-Sartawi (My University, 2001)
The purpose of this study was to investigate computer learning and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students Point of Views. This study mainly concentrated on answering the following questions: 1-What are the obstacles facing computer learning and teaching process in governmental schools in northern directorates of Palestine from teachers and students point views? 2-Are there any statistical differences in computer learning and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students point of views due to their function? 3-Are there any statistical differences in computer learning and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students point of views due to their gender? 4-Are there any statistical differences in computer learning and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students point of views due to teachers experience? 5-Are there any statistical differences in computer learning and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students point of views due to student’s class? 6-Are there any statistical differences in computer learning and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students point of views due to the educational directorates? 7-Are there any statistical differences in computer leaming and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students point of views due to their school place? 8-Are there any statistical differences (or=0.05) between the fields of computer's learning and teaching obstacles in governmental schools in northern directorates of Palestine for teachers and students? To answer the previous questions and to investigate the hypotheses, the researcher chose randomly sample which consisted of (43) teachers who represented (50%) of the population, and he chose a sample which consisted of (930) students who represented (5%) of the population in governmental schools in northern directorates of Palestine during the second semester of the year (1999-2000), And ajury of experts judged the questionnaire, and the reliability of the questionnaire was calculated, and it was (0.91) for the students and (0.89) for the teachers. The researcher used the necessary statistical methods to analyze the data, The study showed; Most obstacles that faced teachers and students were as follows; 1-Equipments field: A-Scarcity of printers machines. B-scarcity of computer’s equipments such as (earphones, voice cards, microphones). 2-Lab environment field: A-bad heating and cooling system in computer labs. B-computer room’s size was not enough for students number. 3-Curriculum field: A-students’ book doesn’t encourage them to read other new materials about computer. B-The computer's book is so large compared with the number of computer’s lessons. 4-Software field: A-The less of leaflets and appendices and guides with the software. B-The educational Arabic software doesn’t go with the new technology of the computer. 5-School circumstances field: A-Scarcity of printing papers for teaching computer. B-There is no Internet service at schools. The results of the study show the following: 1-There are statistical differences (α=0,05) between teachers and students on favor of teachers on school circumstances field, and there are no differences between them on the other fields. 2-There are statistical differences (α=0.05) between male and female teachers on favor of males on software field, and there are no differences.between them on the other fields, and there are no statistical differences (α =0.05) between male and female students on all fields. 3-There are no statistical differences (α=0.05) between teachers on the experience variable. 4-There are statistical differences (α=0.05) between students on class variable on favor of high classes on all fields. 5-There are statistical differences (α=0,05) between students on directorate variable on favor of (Nablus and salfeet) directorates on all fields. 6-There are statistical differences (α=0.05) between town and village from teachers point of views on school place variable on favor of town on lab environment field, and there are no differences between them on the other fields, and there are statistical differences (α=0.05) between town and village from students point of views on school place variable on favor of town on all fields. 7-There are statistical differences (α=0.05) between the fields of the study from teachers and students point of views, and the arrangement of the fields as its difficulty was (school circumstances, equipments, curriculum, software, lab environment). Based on the study findings, the researcher represented some recommendations concerning of the study fields, which are (equipments, lab environment, curriculum, software, and school circumstances).

The purpose of this study was to investigate computer learning and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students Point of Views. This study mainly concentrated on answering the following questions: 1-What are the obstacles facing computer learning and teaching process in governmental schools in northern directorates of Palestine from teachers and students point views? 2-Are there any statistical differences in computer learning and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students point of views due to their function? 3-Are there any statistical differences in computer learning and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students point of views due to their gender? 4-Are there any statistical differences in computer learning and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students point of views due to teachers experience? 5-Are there any statistical differences in computer learning and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students point of views due to student’s class? 6-Are there any statistical differences in computer learning and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students point of views due to the educational directorates? 7-Are there any statistical differences in computer leaming and teaching obstacles in governmental schools in northern directorates of Palestine from teachers and students point of views due to their school place? 8-Are there any statistical differences (or=0.05) between the fields of computer's learning and teaching obstacles in governmental schools in northern directorates of Palestine for teachers and students? To answer the previous questions and to investigate the hypotheses, the researcher chose randomly sample which consisted of (43) teachers who represented (50%) of the population, and he chose a sample which consisted of (930) students who represented (5%) of the population in governmental schools in northern directorates of Palestine during the second semester of the year (1999-2000), And ajury of experts judged the questionnaire, and the reliability of the questionnaire was calculated, and it was (0.91) for the students and (0.89) for the teachers. The researcher used the necessary statistical methods to analyze the data, The study showed; Most obstacles that faced teachers and students were as follows; 1-Equipments field: A-Scarcity of printers machines. B-scarcity of computer’s equipments such as (earphones, voice cards, microphones). 2-Lab environment field: A-bad heating and cooling system in computer labs. B-computer room’s size was not enough for students number. 3-Curriculum field: A-students’ book doesn’t encourage them to read other new materials about computer. B-The computer's book is so large compared with the number of computer’s lessons. 4-Software field: A-The less of leaflets and appendices and guides with the software. B-The educational Arabic software doesn’t go with the new technology of the computer. 5-School circumstances field: A-Scarcity of printing papers for teaching computer. B-There is no Internet service at schools. The results of the study show the following: 1-There are statistical differences (α=0,05) between teachers and students on favor of teachers on school circumstances field, and there are no differences between them on the other fields. 2-There are statistical differences (α=0.05) between male and female teachers on favor of males on software field, and there are no differences.between them on the other fields, and there are no statistical differences (α =0.05) between male and female students on all fields. 3-There are no statistical differences (α=0.05) between teachers on the experience variable. 4-There are statistical differences (α=0.05) between students on class variable on favor of high classes on all fields. 5-There are statistical differences (α=0,05) between students on directorate variable on favor of (Nablus and salfeet) directorates on all fields. 6-There are statistical differences (α=0.05) between town and village from teachers point of views on school place variable on favor of town on lab environment field, and there are no differences between them on the other fields, and there are statistical differences (α=0.05) between town and village from students point of views on school place variable on favor of town on all fields. 7-There are statistical differences (α=0.05) between the fields of the study from teachers and students point of views, and the arrangement of the fields as its difficulty was (school circumstances, equipments, curriculum, software, lab environment). Based on the study findings, the researcher represented some recommendations concerning of the study fields, which are (equipments, lab environment, curriculum, software, and school circumstances).
معوقات تعلم الحاسوب وتعليمه في المدارس الحكومية بمحافظات شمال فلسطين من وجهة نظر المعلمين والطلبة